Trade Unions and innovation - innovative unions? Experiences from selected EU member states - Wim Sprenger (Universität Rostock, Wirtschafts- und Sozialwissenschaftliche Fakultät, Lehrstuhl für ABWL: Wirtschafts- und Organisationspsychologie, 2011)
Which role and facilities are available to trade unions and works councils within the countries of the European Union to co-influence innovation in companies and institutions? This is the main question dealt with in this literature study. Four short country reports will be presented to analyse this question. It will be shown that there are substantial differences between and within countries, due to industrial relations practices, trade union power (density) and poli-cies, government regulation and facilitation, management traditions and activities of other stakeholders.
urn:nbn:de:gbv:28-rosdok_id00002247-7
Keywords: 330; Unternehmen; Innovationsmanagement; Gewerkschaft; Mitbestimmung; Vergleich; Großbritannien; Finnland; Niederlande; Spanien